2023
DOI: 10.1108/ijopm-06-2022-0382
|View full text |Cite
|
Sign up to set email alerts
|

Procurement's role in resolving demand–supply imbalances: an information processing theory perspective

Abstract: PurposeDrawing on information processing theory, the linkage between buffering and bridging and the ability on the part of procurement to resolve demand–supply imbalances is investigated, as well as contexts in which these strategies may be particularly useful or detrimental. Buffering may be achieved through demand change or redundancy, while bridging may be achieved by the means of collaboration or monitoring.Design/methodology/approachThis study employs a hierarchical regression analysis of a survey of 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
(223 reference statements)
0
6
0
Order By: Relevance
“…The modified Lindell-Whitney approach was applied to minimize the chance of the smallest possible correlation occurring by chance among the variables. The Lindell-Whitney results (mean correlation) between the marker variable and other variables (0.047) were processed to adjust the correlation coefficients and their significance level (Laari et al, 2023;Lindell & Whitney, 2001). After the adjustment, all significant coefficients remained significant, which suggested that CMB was not likely to significantly impact the validity of the statistical results.…”
Section: Common Methods Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…The modified Lindell-Whitney approach was applied to minimize the chance of the smallest possible correlation occurring by chance among the variables. The Lindell-Whitney results (mean correlation) between the marker variable and other variables (0.047) were processed to adjust the correlation coefficients and their significance level (Laari et al, 2023;Lindell & Whitney, 2001). After the adjustment, all significant coefficients remained significant, which suggested that CMB was not likely to significantly impact the validity of the statistical results.…”
Section: Common Methods Biasmentioning
confidence: 99%
“…In addition, to examine the extent to which the analysis results might be impacted by reverse causality (Laari et al, 2023), the data were tested using a regression analysis. This analysis checked whether SCV affects buffering by top SC EPS, top SC ESS, FEO, or RSC practices.…”
Section: Endogeneity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…RDT characterizes a firm as an open system to obtain essential resources from outward and inward approaches (Pfeffer and Salancik, 1978). Bridging and buffering responses from RDT provides a rich predictive framework to explain how firms can deal with environmental uncertainty to minimize or overcome resource dependencies and improve their organizational autonomy (Kalaitzi et al, 2019;Laari et al, 2023). According to RDT, IT capabilities should be aligned with response strategies, which means that outward bridging and inward buffering may require support from corresponding structural IT capabilities (Kalaitzi et al, 2018).…”
Section: Bridging Versus Bufferingmentioning
confidence: 99%
“…Bridging and buffering responses from RDT provides a rich predictive framework to explain how firms can deal with environmental uncertainty to minimize or overcome resource dependencies and improve their organizational autonomy (Kalaitzi et al. , 2019; Laari et al. , 2023).…”
Section: Theory and Constructsmentioning
confidence: 99%